PEMBUATAN KATALOG DWI BAHASA TENTANG TENUN IKAT SUMBA TIMUR - Itha Priyastiti; Raynesta Mikaela Indri Malo; Suryani Kurniawi Kahi Leba Kapoe (Universitas Mataram, 2023)
East Sumba is well known for its ikat weaving, among other cultural tourism potentials. As a cultural legacy, attempts are required to introduce ikat to an enormous scope nationwide and globally. Unfortunately, the ikat has only been presented through occasional festivals or exhibitions. Another challenge is that there need to be more archives containing information about ikat in English. Therefore, to address the challenges, this community outreach activity aims to introduce ikat to a broader audience by designing a catalog in bahasa Indonesia and English. The catalog contains information, including patterns, materials, and philosophical meanings of East Sumba ikat, and was distributed to eight galleries in Waingapu, which are the leading destinations for domestic and international tourists visiting East Sumba. In addition, two catalogues were distributed to the tourism office as the library collection and archive to allow access to the public who need information about ikat.